Effectiveness and Challenges of the Regulatory Framework for Eliminating Gender Based Violence in Indonesia: Efektivitas dan Tantangan Kerangka Regulasi Penghapusan Kekerasan Berbasis Gender di Indonesia - Moh. Riziq; Thobary, Amim; Nurillah, Isma; Manaqib, Ulil (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
Gender-based violence remains a serious issue despite the enactment of various legal instruments and policies. This article aims to comprehensively evaluate the effectiveness of the regulatory framework for eliminating gender-based violence by examining the gap between legal norms and implementation practices. This study uses a qualitative approach, drawing on literature reviews and policy analyses of regulatory documents, news sources, and relevant academic publications. The analysis was conducted using a policy implementation and governance framework for gender-based violence. The results of the study indicate that Indonesia has a relatively progressive regulatory and institutional framework, but its implementation remains limited. The effectiveness of policies is not determined solely by the completeness of norms, but also by the integration of service systems, service standardization, and support for normative change. This article offers a comprehensive analytical framework for assessing the effectiveness of policies to eliminate gender-based violence in Indonesia.